IMMUNOLOGICAL ASSESSMENT OF THE HULLED BARLEY COLLECTION ACCORDING TO ITS RESISTANCE TO LEAF DISEASES IN THE SOUTHERN PART OF THE ROSTOV REGION - E. S. Doroshenko; Ed. S. Doroshenko (Зерновое хозяйство России)
In the conditions of artificial infectious background of the laboratory of plant immunity and protection (Agricultural Research Center “Donskoy”) there has been conducted an immunologic estimation of hulled barley samples of ARIR collection. There has been estimated resistance to the following pathogens: powdery mildew (pathogen Erysiphegraminis f. hordei), barley net blotch (Pyrenophorateres (Died.) Drechsler [Drechslerateres (Sacc.) Shoemaker]) and barley dark-brown blotch (Bipolaris sorokiniana (Sacc.), Shoemaker [Cochliobolussativus (S. Ito &Kurib) Drechsler ex Dastur, Helminthosporiumsativum Pammel, C.M. King & Bakke]). The study of disease manifestation was done in 2016–2017. The results allow estimating variety resistance in the extreme infectious conditions similar to epiphytotinous conditions. As a result there have been identified the samples ‘Dublet’ (Belorussia), ‘Omsky golozerny 1’ (Russia), ‘К-26648’ (Pakistan), ‘Back CDC’,’CDC VC Ywire’, ‘CDC Dawn’ (Canada), ‘К-3038’ (Dai Mai), ‘Orgeniepetite’ (France), ‘NB-OWA’ (Nepal) and others that showed resistance and slight susceptibility to powdery mildew. The samples ‘Back CDC’, ‘Bowman’ (Canada), ‘84469/70’, ‘К-303’ (Dai Mai), ‘Dublet’ (Belorussia), Brunее (Ethiopia), ‘Orgeniepetite’ (France) and others showed resistance to barley net blotch. The samples ‘Dublet’, ‘Omsky golozerny 1’,  ‘Omsky golozerny 2’, ‘Yudinsky 1’, ‘К-26648’, ‘84469/70’, ‘Orgeniepetite’, ‘CDC Dawn’, ‘NB-OWA’, ‘К-3038’, ‘CDC VC Ywire’, ‘E.E.B.N.46’ demonstrated a complex resistance to both pathogens and they are recommended for use in the breeding programs on immunity.